What's the big idea? Cramér–Rao inequality and Rao distance - Plastino, Ángel Ricardo (2020)
Angel Ricardo Plastino and Angelo Plastino give a brief introduction to two key developments in statistics that originate with C. R. Rao's 1945 paper, “Information and accuracy attainable in the estimation of statistical parameters”.